Oral Health Behavior of Parents as a Predictor of Oral Health Status of Their Children. (8th May 2013) - Bozorgmehr, Elham; Hajizamani, Abolghasem; Malek Mohammadi, Tayebeh
Abstract : Introduction . It is widely acknowledged that the behavior of parents affects their children's health. This study aimed to evaluate the relationship between oral health behavior of parents and oral health status and behavior of their children in a sample of preschool children in Iran. Method and Material . A random sample of over-five-year-old preschool children and their parents were enrolled in the study. Selection of schools was by clustering method. Parents were asked to fill a piloted questionnaire which included demographic characteristics, socioeconomic status, oral health behaviors of children and their parents. Oral health status of children was examined. The parent and their children oral health relationship were tested using regression and correlation analysis. Results . About 222 parents and children participated in the study. There was a significant relationship between history of having dental problems in parents and dmft index in their children (P = 0.01 ). There was a significant relationship between parental frequency of tooth brushing and child frequency of tooth brushing (P = 0.05 ); however, there was no significant relationship between parental frequency of dental visits and those of their children (P = 0.1 ). Conclusion . The study concluded that some important health behaviors in parents, such as tooth brushing habits are important determinants of these behaviors in their young children. So promoting parent knowledge and attitude could affect their children oral health behavior and status.